English as a language of instruction in the context of an inland university in Mato Grosso Do Sul-Brazil - Chagas, Lucas Araujo; Guimarães, Thiago Mariano (Revista Letras Raras, 2024)
In this article, we aim to problematize the adoption of English as a language of instruction in Higher Education and identify possible representations that the English Language has reverberated in the academic practices of a university located in the inland of Mato Grosso do Sul. Immersed in the assumptions of Applied Linguistics (Moita Lopes, 2006), we begin the text by problematizing the equity between inland and metropolitan universities in promoting movements of Internationalization in Higher Education, multilingualism, and interculturality. Next, we conduct a theoretical review of the different elements that permeate the adoption of English as a language of instruction in universities, considering the movements of Internationalization of Higher Education, go into the concept of representation, describe the research context, and develop some analyses based on statements extracted from Guimarães' (2023) corpus. Finally, we offer some concluding remarks on the representations surrounding the (non) adoption of English as a language of instruction in the researched context.